Chemical composition of Italian propolis of different ecoregional origin. Issue 5 (20th October 2018) - Gardini, Silvia; Bertelli, Davide; Marchetti, Lucia; Graziosi, Riccardo; Pinetti, Diego; Plessi, Maria; Marcazzan, Gian Luigi
Abstract : The aim of this work was studying and identifying the main physicochemical properties and active constituents of Italian propolis derived from resident hives throughout the peninsula. The data, potentially useful to establish important propolis quality criteria, were compared to those typical of poplar type propolis and used to build a classification model to link the propolis characteristics to its ecoregion of origin. HPLC-ESI-TQ MS was used to quantify 21 phenolic compounds in propolis extracts. Considering the bioactive substances and the antioxidant activity, statistically significant characteristics can distinguish propolis from the considered Italian ecoregions: Mediterranean and temperate division and, due to the high presence of poplar trees, the Po plain province as part of temperate division. Chrysin is the most abundant flavonoid in all the samples followed by galangin and pinocembrin. Regarding phenolic acids the samples from temperate and Mediterranean ecoregions are characterized by high amount of ferulic and isoferulic acids. Composición química del propóleos italiano de diferente origen ecorregional El objetivo de este trabajo fue el estudio e identificación de las principales propiedades fisicoquímicas y componentes activos del propóleos italiano derivados de las colmenas residentes en toda la península. Los datos, potencialmente útiles para establecer importantes criterios de calidad del propóleos, se compararon con los típicos de los álamos y se utilizaron para construir un modelo de clasificación que vinculara las características del propóleos con su ecorregión de origen. Se utilizó HPLC-ESI-TQ MS para cuantificar veintiún compuestos fenólicos en extractos de propóleos. Considerando las sustancias bioactivas y la actividad antioxidante, las características estadísticamente significativas pueden distinguir al propóleos de las ecorregiones italianas consideradas: división mediterránea y templada y, debido a la alta presencia de álamos, la provincia de la llanura del Po como parte de la división templada. La crisina es el flavonoide más abundante en todas las muestras, seguido de la galangina y la pinocembrina. En cuanto a los ácidos fenólicos, las muestras de las ecorregiones templadas y mediterráneas se caracterizan por una elevada cantidad de ácidos ferúlicos e isoferúlicos.